(3BQGA aj abg GdJNda (B:s (3GdYQH hGdZQH aj YUQ GdYhdeI (B/s - (3GdfbjH, NdOhf MSfs ((3HjQhJ(B: s (3OGQ GdSGaj(B, s, 2002)
(3age JNda GdeLJeY GdeOfj , abQ GdSjGSI, GdJWHjY, GdehGLgI GdJGQjNjI eY GdYQH, KbGaI GdJNda, GdKbGaI JSdjI hGdSjGSI hGbY hgejs
Keywords: (3GdJNda GdGLJeGYjs; (3GdJNda GdGbJUGOjs; (3GdabQs